2018
DOI: 10.1002/hbm.24183
|View full text |Cite
|
Sign up to set email alerts
|

Altered intra‐ and inter‐network functional coupling of resting‐state networks associated with motor dysfunction in stroke

Abstract: Motor functions are supported through functional integration across the extended motor system network. Individuals following stroke often show deficits on motor performance requiring coordination of multiple brain networks; however, the assessment of connectivity patterns after stroke was still unclear. This study aimed to investigate the changes in intra- and inter-network functional connectivity (FC) of multiple networks following stroke and further correlate FC with motor performance. Thirty-three left subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 46 publications
(68 reference statements)
6
62
2
Order By: Relevance
“…Eleven RSNs were identified out of all 40 ICs by spatial correlations in accordance to previous research (Smith et al, 2009; Peraza et al, 2017; Huang et al, 2018; Zhao et al, 2018). The RSNs included these networks were AN, pDMN, aDMN, rFPN, lFPN, DAN, MVN, LVN, SMN, pTMN, and CB (Figure 2).…”
Section: Resultssupporting
confidence: 73%
“…Eleven RSNs were identified out of all 40 ICs by spatial correlations in accordance to previous research (Smith et al, 2009; Peraza et al, 2017; Huang et al, 2018; Zhao et al, 2018). The RSNs included these networks were AN, pDMN, aDMN, rFPN, lFPN, DAN, MVN, LVN, SMN, pTMN, and CB (Figure 2).…”
Section: Resultssupporting
confidence: 73%
“…As we know, the DMN controls both primary perception and advanced cognition and is responsible for the integration of these two (Zhao et al, 2018 ). Studies by Chen et al ( 2018 ) indicated that compared with healthy controls, patients with hearing impairment showed reduced spontaneous neuronal activity in the precuneus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several FC studies have revealed potential neural mechanisms of spontaneous and rehabilitation-driven motor recovery after stroke (Park et al., 2011; Rehme et al., 2011a; Volz et al., 2016). Motor execution requires functional interactions between distributed but related brain regions (Zhao et al., 2018b), and focal lesions may disrupt remote cortical networks and result in impaired functional processes (Siegel et al., 2016; Wang et al., 2014). However, to date, the nature and relevance of abnormal network reorganization for different hand outcomes after chronic subcortical stroke remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Using the ICA approach, one study found that well-recovered stroke patients showed disrupted connectivity within and between networks in the sensory processing, dorsal attention, frontoparietal, and default mode networks (Wang et al., 2014). Another study found that stroke patients with severe to mild motor deficits showed abnormal connectivity in more widespread networks, such as the motor, visual, dorsal attention, executive control, and default mode networks (Zhao et al., 2018b). Furthermore, Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation